Advances in alginate impression materials: a review - Alaghari, Sahithi; Velagala, Surekha; Alla, Rama Krishna; AV, Ramaraju (International Journal of Dental Materials, 2019)
Alginate is an elastic irreversible hydrocolloid which has various applications in dentistry. The applications of alginates include making impressions of edentulous and partially edentulous arches, duplication of casts, and for making study models. Alginates possesses numerous vital properties such as hydrophilicity, ability to record finer details, elastic recovery and inexpensive; makes this material widely used in dentistry. Though alginate is the most commonly used impression material, it has some inherent disadvantages. Alginates contain low-density fine filler particles, which may arise in the form of dust and inhalation these dust particles may cause respiratory problems. Further, they are highly dimensionally unstable due to syneresis & imbibition. Besides, alginates do not adhere to non-perforated trays, low viscosity resulting in gag reflex in some patients, and the inability to identify the correct consistency to load. Several modifications were made in the composition of conventional alginates to address their shortcomings. This article reviewed various recent advances in the alginate impression materials and their performance.